Dana Gardner Munro and Ralph L. Woodward: two American visions of Central America in the early and late twentieth century - Molina Jiménez, Iván (2015)
This article compares the visions of Central America present in two classic studies written by U.S. scholars: The Five Republics of Central America (1918) by Dana G. Munro, and Central America, a Nation Divided (1976) by Ralph Lee Woodward. Besides considering the differences and similarities between them, I also analyze the insertion of these two books in the intellectual marketplace and their critical background to discuss the role played by the United States in Central America.